Demonstration of Mg(NO3)2·6H2O-based composite phase change material for practical-scale medium-low temperature thermal energy storage. (15th June 2020) - Zhao, B.C.; Li, T.X.; He, F.; Gao, J.C.; Wang, R.Z.
Abstract: This work focuses on the industrialization-oriented investigation of a latent heat storage using a magnesium nitrate hydrate-based composite phase change material. Three aspects of studies are included: (i) characterizations on the thermal-physical properties of the composite, (ii) explorations on the supercooling stability of the composite within continuous thermal cycles, and (iii) evaluations on the thermal performance of a pilot-scale storage unit. The results indicate that the freshly-prepared composite has a fusion heat of 147.9 ± 0.5 J g −1, a storage capacity of 253.5 ± 0.9 J g −1 within 70–110 °C. The PCM presents no significant degradation after 100 thermal cycles. The material performs a better supercooling stability than pure magnesium nitrate hexahydrate. The designed latent heat storage unit can achieve stable charges and discharges with an effective heat storage density of 33.5 ± 2.6 kWh m −3, a thermal efficiency of 88.1 ± 9.6% and a thermal loss of around 10% during a daily operation. In addition, the storage unit performs a higher latent heat release concentration as discharging rate drops and its effective storage capacity within 80–85 °C is over 4.3 times of water storage. The density of the device within a daily operation can be effectively improved by reducing the thickness of thermal insulation layer. Graphical abstract: Image 1 Highlights: Characterizes the thermal-physical properties of a magnesium nitrate hydrate-based composite. Investigates the supercooling stability of the composite during a 100-time thermal cycles. Develops a 140-kWh latent heat storage device using the composite for practical applications. Evaluates the charging/discharging and thermal insulation performance of the storage device.